Pediatric Dental Management of Child with Autism Spectrum Disorder under General Anesthesia: A Case Report (Journal of Dentistry and Allied Science, 2023)
Early childhood caries considered to be the most common chronic disease of the child and resulting in gross destruction of the dentition. It gives rise to severals problems like functional problem, pain, retard growh and aesthetic problems. Special health care needs childs suffers more due to improper dietary habit and lack of proper oral hygiene maintenance. Behavior management of non communicative child like child with autism spectrum disorder are very difficult to manage in conventional dental setting. Dental treatment under general anesthesia considered to be a good option for management of such cases. Dental treatment under general anesthesia have multiple advantages like immediate pain relief, extensive treatment in shorter period of time and patient compliance is not required. This case report demonstrated dental treatment of a child with autism spectrum disorder under general anesthesia.Journal of Dentistry and Allied Science, Vol. 6 No 2: 30-34